(untitled) (Huellas, 2022)
The community-based modality is consolidating as a way of organizing tourism in rural areas, although its conceptualization and implementation is diverse. The State has a relevant role in the promotion, planning and extension of tourism in a territory. For this reason, we are interested in analyzing how the notions of community tourism are constructed –and regulated– from public policies based on regulatory frameworks. Thus, in this paper we analyze the course of the institutionalization of community tourism in Argentina based on its existing national and provincial legislation. As a result, we observe a diversity of ways of defining rural tourism and the participation of communities based on what is meant by rural tourism and what sectors of the communities are included.